Study on Model of Penetration into Thick Metallic Targets with Finite Planar Sizes by Long Rods. (13th March 2021) - Wang, Juan; Zhao, Junhai; Zhang, Jianhua; Zhou, Yuan
Abstract : A finite cylindrical cavity expansion model for metallic thick targets with finite planar sizes, composed of ideal elastic-plastic materials, with penetration of high-speed long rod is presented by using the unified strength theory. Considering the lateral boundary and mass abrasion of the target, the penetration resistance and depth formulas are proposed, solutions of which are obtained by MATLAB program. Then, a series of different criteria-based analytical solutions are obtained and the ranges of penetration depth of targets with different ratios of target radius to projectile radius ( r t / r d ) are predicted. Meanwhile, the numerical simulation is performed using the ANSYS/LS-DYNA finite element code to investigate the variations in residual projectile velocity, length, and mass abrasion. It shows that various parameters have influences on the antipenetration performance of the target, such as the strength coefficient b, r t / r d, the shape of the projectile nose, and the impact velocity of the projectile, among which the penetration depth has increased by 18.95% as b  = 1 decreases to b  = 0 and has increased by 32.28% as r t / r d  = 19.88 decreases to r t / r d  = 4.9.